Penerapan Word of Mouth dalam Membangun Kepercayaan Masyarakat dan Brand Image Universitas pada Keputusan Pemilihan UPBJJ-UT Ternate: The Application of Word of Mouth in Building Community Trust and University Brand Image on Selection Decision for UPBJJ-UT Ternate - Anfas Anfas; Ida Hidayanti; Mohbir Umasugi; Ibnu Sina Hi. Yusuf (Laboratorium Rekayasa Sosial, Jurusan Sosiologi, FISIP Universitas Bangka Belitung, 2021)
This study examines the application of word of mouth to build community trust and university brand image on the community selection decision for UPBJJ-UT Ternate. The samples were obtained from eight regencies in North Maluku Province through a survey method aided with Smart PLS 3.8 analysis. In addition to the insignificant effect of university image on community selection decision, the findings indicated that (1) university image has a significant effect on word of mouth, (2) community trust has a significant effect on word of mouth, (3) community trust has a significant effect on selection decision, and (4) word of mouth has a significant effect on community selection decision.